Transformational Leadership and Readiness for Change on the Performance of Bhakti Husada II Hospital - Maya Apriani; Dede R Oktini; Tasya Aspiranti (Penerbit Goodwood, 2026)
Purpose: This study aimed to determine the effect of transformational leadership and readiness for change on employee performance at Bhakti Husada II Hospital Purwakarta. Methodology/approach: The research design is verificative and uses a case study approach. The sampling technique used was proportional stratified random sampling with the Lemeshow formula, resulting in a sample size of 161 employees at Bhakti Husada II Hospital, Purwakarta. The research instrument used an online questionnaire consisting of demographic and research-related questions. Hypothesis testing for the study variables was conducted using a multiple linear regression analysis. Results: The results of the study indicate that transformational leadership and readiness for change have a positive effect on employee performance. The findings show that both transformational leadership and readiness for change simultaneously and partially have a significant influence on the staff performance at Bhakti Husada II Hospital Purwakarta. Conclusions: This study concludes that strengthening transformational leadership practices and enhancing employee readiness for change are key strategies for improving staff performance. Hospital management should focus on leadership development programs and change management initiatives to sustain high-quality performance. Limitations: This study was limited to one hospital, relied on self-reported questionnaires that may have caused bias, examined only two variables, and used a cross-sectional design that restricted causal interpretation. Contributions: This study confirms the positive impact of transformational leadership and readiness for change on performance, offering practical insights for hospitals.